The Influence of Compensation and Motivation on Employee Performance at Freshmart Bahu Mall Manado - Laurens Mambu; Hentje Kandati; Inneke Makaliwe (Pusat Riset dan Inovasi Nasional, 2025)
Compensation and motivation are two important factors in the organization of a company. High attention to both of these is expected to have an impact on increasing employee performance in providing services to consumers. However, from the results of observations, it appears that there are still employees who are still lacking in motivation in providing services to consumers: 1) Employees at Freshmart Bahu Mall Manado have not become professional human resources in providing services to consumers; 2) There are still employees who have low motivation. This study aims to 1) determine the effect of compensation on employee performance at Freshmart Bahu Mall Manado. 2) to determine the effect of motivation on employee performance at Freshmart Bahu Mall Manado, 3) to determine the effect of compensation and motivation together on employee performance at Freshmart Bahu Mall Manado. This study uses a correlational method. The data analysis conducted provides the following conclusions: 1) Compensation has a significant effect on employee performance at Fresh Mart Bahu Mall Manado, 2) Motivation has a significant effect on employee performance at PT. Fresh Mart Bahu Mall Manado, 3) Simultaneously, both compensation and motivation have an effect on employee performance at Fresh Mart Bahu Mall Manado.